If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x-2)/3+(x-3)/2=5/6
We simplify the equation to the form, which is simple to understand
(3x-2)/3+(x-3)/2=5/6
Simplifying:
(3x-2)/3+(x-3)/2=0.833333333333
Reorder the terms in parentheses
(+1x-0.666666666667)+(x-3)/2=0.833333333333
Remove unnecessary parentheses
+1x-0.666666666667+(x-3)/2=0.833333333333
Reorder the terms in parentheses
+1x-0.666666666667+( + 0.5x-1.5)=0.833333333333
Remove unnecessary parentheses
+1x-0.666666666667 + 0.5x-1.5=0.833333333333
We move all terms containing x to the left and all other terms to the right.
+1x + 0.5x=0.833333333333 + 0.666666666667+1.5
We simplify left and right side of the equation.
+1.5x=+3
We divide both sides of the equation by 1.5 to get x.
x=2
| 4x-7(-3x-11)=-173 | | 1080x^3+3=0 | | -2(5t-2)+4t=3t-7 | | 2a=44 | | 3(4x+7)=12x+21 | | 15(t-4)+3=6(3t+5)-12 | | 9/22=(5w+1)/(w+3) | | 9x+9y=4 | | Z-5=8 | | 2(x-8)=4(x-4) | | 0.5(-6x+8)=3(x+2)+1 | | 12y+24-y=4y+16 | | 4(1+2)(-3)=5+c*1 | | 3t+18=9 | | 7+2t-5=7t+5-4t | | 8x^2-24+18y^2=0 | | 4(1+2)-3=5+c*1 | | 3X-2(-x-3)=-44 | | (4t^3-5t-1)/(2t-1) | | 4b^4-26b^2-90=0 | | 13x+5=13x-5 | | 5*1+8=71+b*1 | | -15+w=6 | | 5a-(8a)=4a-10 | | 1/3(15x-9)+1/5(25x+5) | | 8x^8-8=0 | | -5a+24+9a=3a-7a | | 9x+2/x+3=4 | | 8b+2=3b+12 | | 5*9+8=71+b*9 | | 1/8-1/2 | | -3(4y-8)-y=-4(y-4) |